Methodology of Tax Management in the Economic System of the State - Tatyana V. FEOKTISTOVA; Yuri N. VOROBEV (Communications of International Proceedings, 2020)
The article contains the author’s position on the key issues of understanding the tax management methodology. The author reveals the relationship between taxation and the economic system of the state in its broad sense. The author reveals the influence of deviations from the classical directions of the development of scientific cognition on the practice of tax management.
Keywords: Tax Management; Science; Methodology.